1967
DOI: 10.1161/01.res.21.3.305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Propranolol and Its Stereoisomers upon Coronary Vascular Resistance

Abstract: Responses of the coronary vascular bed to propranolol and its stereoisomers were studied in dogs anesthetized with allobarbital and urethane. The circumflex coronary artery was cannulated and perfused at a constant rate with blood from a femoral artery, coronary perfusion pressure being monitored as an index of coronary vascular resistance. dl -Propranolol (0.5 mg/kg iv) increased coronary vascular resistance and simultaneously reduced myocardial contractile force, heart rate, and syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1969
1969
1997
1997

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Presumably the 3-adrenoceptor mediated vasodilator stimulus was removed by denervation at the time of transplantation. In the present studies, the larger dose of propranolol (30,ug/min) produced a small negative inotropic effect due either to the inhibition of 1-receptor stimulation by circulating catecholamines (Davis, MacDonald & Mason, 1969) or to a direct depressant effect on the transplanted heart or to both (Whitsitt & Lucchesi, 1967 both Cohen et al (1970) in the rat heart and Massingham & Nasmyth (1972) in the frog heart, who found that the positive inotropic effects of aminophylline were not influenced by 13-receptor blockade with propranolol. However, Marcus et al (1972) produced ,-adrenoceptor blockade in the cat isolated papillary muscle with non-depressant doses of propranolol and reported that this reduced the maximum positive inotropic action of theophylline by 40%.…”
Section: Aminophylline and 3-adrenoceptor Blockadesupporting
confidence: 43%
“…Presumably the 3-adrenoceptor mediated vasodilator stimulus was removed by denervation at the time of transplantation. In the present studies, the larger dose of propranolol (30,ug/min) produced a small negative inotropic effect due either to the inhibition of 1-receptor stimulation by circulating catecholamines (Davis, MacDonald & Mason, 1969) or to a direct depressant effect on the transplanted heart or to both (Whitsitt & Lucchesi, 1967 both Cohen et al (1970) in the rat heart and Massingham & Nasmyth (1972) in the frog heart, who found that the positive inotropic effects of aminophylline were not influenced by 13-receptor blockade with propranolol. However, Marcus et al (1972) produced ,-adrenoceptor blockade in the cat isolated papillary muscle with non-depressant doses of propranolol and reported that this reduced the maximum positive inotropic action of theophylline by 40%.…”
Section: Aminophylline and 3-adrenoceptor Blockadesupporting
confidence: 43%
“…In this connection, in animals at rest, propranolol can produce an increase in subendocardial flow in an ischemic zone (Becker et al, 1971;Vatner et al, 1977), and at rest when heart rate slows after propranolol, both regional function and total coronary flow improve (Tomoike et al, 1978b). Finally, in normal regions of the heart, a major decrease in coronary blood flow occurs after propranolol primarily because of decreased myocardial oxygen consumption, although propranolol may directly increase coronary vascular resistance (Whitsitt and Lucchesi, 1967). Thus, coronary "steal" during exercise may be diminished by reduction of the workload in normal regions produced by propranolol (Guyton et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Propranolol at the dose employed (3 mg/kg) decreases ventricular contractility both by eliminating sympathetic stimulation of the heart and also by a direct depressing action on the myocardium (17,18). Propranolol has also been shown to interfere directly with a mechanism facilitating transfer of calcium ion into the myocardial cell (43) and this agent may by this mechanism also lower intracellular calcium stores.…”
Section: Discussionmentioning
confidence: 99%
“…Seven of the eight dogs were studied also in the conscious state after administration of a large dose of propranolol, 3.0 mg/kg. This dose of propranolol is considerably in excess of that required to produce blockade of beta adrenergic receptors and exerts a direct depressant effect on the myocardium (17,18). In both of these latter circumstances, end diastolic diameter was maintained constant by saline infusion as heart rate was increased.…”
Section: Introductionmentioning
confidence: 99%